Peer contagion processes for problematic internet use among Chinese college students: A process model involving peer pressure and maladaptive cognition. (January 2019) - Zhou, Nan; Ma, Shanshan; Li, Xiaomin; Zhang, Jintao; Liang, Yue; Yu, Chengfu; Geng, Xiaomin; Meng, Jiangbei; Yuan, Xiaojiao; Cao, Hongjian; Fang, Xiaoyi
Abstract: Although affiliation with deviant peers is among the most salient risk factors for college students' maladjustment, few studies have examined the possible peer contagion processes for problematic Internet use and the underlying mechanisms explaining how peer factors may shape the development of problematic Internet use. Based on data from 2516 Chinese undergraduate students (mean age = 18.56 years, SD  = 0.84; 38.16% female) across their four college years and utilizing lagged latent difference score analyses, this study tested a process model to elucidate how peer Internet overuse and peer pressure on Internet use may contribute to Chinese undergraduates' problematic Internet use via shaping their maladaptive cognitions over Internet use. Results indicated that peer Internet overuse predicted subsequent increases in students' peer pressure on Internet use, which in turn, were linked with students' elevated problematic Internet use via maladaptive cognitions over Internet use. This dynamic cascade process was robust even after considering a series of potential confounding variables and the prospective associations among the key variables of interest. Such findings shed light on the peer contagion processes for the development of Chinese college students' problematic Internet use, and provide empirical evidence supporting the call for integrating peer factors into prevention and intervention programs aimed at reducing the incidence and severity of college students' problematic Internet use. Highlights: Peer contagion processes for problematic Internet use were examined. A latent difference scores model based on four annual waves of data were used. Peer Internet overuse predicted Chinese college students' problematic Internet use. Peer pressure was identified as a significant mediator. Maladaptive cognitions was identified as a more proximal predictor.